The Effect Of Implementing The Problem-Based Learning (PBL) Model On Enhancing Students’ Active Participation And Critical Thinking Skills - Fitri, Ramdani Aidiatul; Sri Wahyuni; Hajriana Arfah; Zahratul Fikni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the implementation of Problem-Based Learning (PBL) to enhance the micro-cognitive critical thinking processes of vocational students during the pre-writing and drafting phases of English for Specific Purposes (ESP) instruction. Conventional language instruction often isolates learning from authentic vocational contexts, triggering severe difficulties in translating technical ideas into structured texts. Addressing this empirical gap, a qualitative case study was conducted with tenth-grade students in the Agribusiness of Agricultural Product Processing (APHP) program at SMKN 1 Kotaraja. Data gathered through classroom observations, writing artifacts, and retrospective interviews from 32 participants, including six focal students, were analyzed using an interactive qualitative framework. The findings demonstrate that authentic agribusiness problem scenarios embedded within the PBL syntax effectively stimulate Facione’s core critical thinking indicators—interpretation, analysis, evaluation, and inference. Students successfully deconstructed complex agricultural issues, managed cognitive loads collaboratively, and produced coherent argumentative texts. Theoretically and practically, this study proves that integrating PBL into ESP instruction bridges the gap between vocational problem-solving and professional language proficiency, offering a validated pedagogical blueprint for modern vocational education.